Pelatihan Pemeliharaan Website Sistem Informasi Rukun Warga - Nurhasanah Nugraha, Siti; Herliawan, Irwan; Rahmawati, Ami; Ambarsari, Diah Ayu; Fikri, Muhamad (Indonesian Journal for Social Responsibility, 2023)
The rapid development of technology has made information dissemination not only through offline media, but also online media contribute to the provision of information. One of the areas that use information technology in the service process is Rukun Warga (RW). RW 13 is one of 22 RW’s in Cipinang Melayu Village, which currently uses a manual system in the service process. In addition, the problem faced by the administrators of RW 13 is the lack of knowledge in managing and maintaining the website. As a form of service to the surrounding community, a group of lecturers from Universitas Nusa Mandiri conducted a community service activity in the environment of RW 13 in the form of training activities on website maintenance of the Neighborhood Information System. This activity aims to make the participants understand how important it is to maintain the website so that the website will continue to run optimally. Participants in this community service activity are RT administrators, RW administrators, and youth from RW 13 youth organizations. The method used in this community service activity is interactive theoretical training, while the practical method uses simulation and question and answer methods. The evaluation results of the community service activities conducted based on the completion of questionnaires by 20 participants can be concluded that the participants are satisfied with the implementation of this training activity so that it can increase the knowledge, understanding and skills of the participants on the importance of website maintenance. In addition, the participants argue that this community service activity in the form of training has met the expectations of the participants, can increase the knowledge and skills of the participants, and can help solve existing problems.